2019
DOI: 10.3389/fneur.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Pupillometry Methods for Assessing Photoreceptor Health in Retinal and Optic Nerve Diseases

Abstract: The pupillary light reflex is mediated by melanopsin-containing intrinsically-photosensitive retinal ganglion cells (ipRGCs), which also receive input from rods and cones. Melanopsin-dependent pupillary light responses are short-wavelength sensitive, have a higher threshold of activation, and are much slower to activate and de-activate compared with rod/cone-mediated responses. Given that rod/cone photoreceptors and melanopsin differ in their response properties, light stimuli can be designed to stimulate pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 141 publications
0
70
0
1
Order By: Relevance
“…Analyzing these relative changes minimized the influence of preexisting pupil sizes and the impact of dark-adapted responses. Another limitation of our study is that with the current pupil measurement protocol, we are not able to completely isolate the different photoreceptor contributions to the physiological pupil responses, as was recently shown by others (McAdams et al, 2018; Rukmini et al, 2019). However, a methodological comparison revealed comparable results for the PIPR and this different method, called silent substitution (Estevez and Spekreijse, 1982; Spitschan and Woelders, 2018; Tsujimura et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Analyzing these relative changes minimized the influence of preexisting pupil sizes and the impact of dark-adapted responses. Another limitation of our study is that with the current pupil measurement protocol, we are not able to completely isolate the different photoreceptor contributions to the physiological pupil responses, as was recently shown by others (McAdams et al, 2018; Rukmini et al, 2019). However, a methodological comparison revealed comparable results for the PIPR and this different method, called silent substitution (Estevez and Spekreijse, 1982; Spitschan and Woelders, 2018; Tsujimura et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…A study by Gamlin et al showed that by blocking rods and cones in nonhuman primates, the sustained pupil response was largest after light exposure, with a peak wavelength at the maximal sensitivity of ipRGCs, following the sensitivity curve of melanopsin with a peak at 482 nm (Gamlin et al, 2007). Several attempts were made to physiologically isolate the photoreceptor contributions, especially the contribution from ipRGCs (for a review, see Rukmini et al, 2019). An action spectrum of the pupil response revealed peak sensitivity also around 480 nm in rod and coneless mice (Lucas et al, 2001) and in humans (Bouma, 1962; Gamlin et al, 2007), further indicating the melanopsin-driven impact on the pupil response to short-wavelength light stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…But the senescence of the lens does not selectively reduce the mRGCs responses to intense blue light and is well-preserved, in spite of its decreased lens transmittance in aging and cataract (51). Different retinal and optic nerve conditions can affect PLR and using chromatic pupillometry it is possible to localize the loss of photoreceptoral function i.e., inner or outer retina (107). Primary open angle glaucoma is associated with decreased PLR in response to exposure to both red and blue light with decreased PIPR for blue light (28, 70), while retinal dystrophies affecting rods and cones lead to decreased PLR responses to red and low intensity blue light with an increased PIPR to bright blue light stimulus (108, 109).…”
Section: Limitations Of Previous Pupillometric Studies In Admentioning
confidence: 99%
“…Moreover, recent studies show that in mesopic and scotopic adaption the rods are involved in the phasic and sustained pupil light response 27,57,63,75,76 . At higher retinal illumination levels the melanopsin activated ipRGCs are dominating this contribution 2,74 .The time until the pupil diameter has reached its' steady state depends on the used spectrum composition 73,[77][78][79] . McDougal and Gamlin 30 showed, by fitting a custom receptor weighting function, that cones contribute little to the pupil light response after 30 s. The derived function for determining the receptor contribution did not consider the pupil light reflex's opponent channels.…”
mentioning
confidence: 99%